Comorbidities of alopecia areata: a population‐based cohort study. (1st June 2021) - Egeberg, A.; Anderson, S.; Edson‐Heredia, E.; Burge, R.
Summary: Background: Previous studies have associated alopecia areata (AA) with a number of comorbidities. However, the timing between AA and the development of such comorbidities remains poorly understood. Aim: To examine the temporal relationship between AA diagnosis and comorbidity development in Denmark. Methods: A Danish nationwide register‐based cohort study was performed on all individuals diagnosed with AA between 2007 and 2016 ( n = 1843), and each patient was matched for age and sex with 10 healthy controls (HCs). Time between AA and comorbidity development was assessed, and incidence rate ratios (IRRs) were calculated to assess risk of comorbidity following initial AA diagnosis. Results: Use of antidepressant and anxiolytic drugs were mostly started prior to AA diagnosis, and these drugs were used more frequently before than after diagnosis with AA. Additional frequent comorbidities included thyroid disease, hyperlipidaemia, type 2 diabetes and asthma. Most comorbidities occurred prior to AA diagnosis; however, among those that occurred after AA diagnosis, antidepressants (IRR = 1.26, 95% CI 1.01–1.56), anxiolytics (IRR = 1.55, 95% CI 1.17–2.05), atopic dermatitis (AD; IRR = 9.41, 95% CI 4.00–22.16), asthma (IRR = 2.17, 95% CI 1.46–3.21), vitiligo (IRR = 30.35, 95% CI 6.13–150.39), Crohn disease (CD; IRR = 3.04; 95% CI 1.22–7.56) and thyroid disease (IRR = 2.38; 95% CI 1.72–3.29) occurred more frequently among patients with AA compared with controls. Conclusion: A diagnosis of AA was significantly associated with risk of several comorbidities, most notably vitiligo, AD and CD. Nonetheless, the majority of patients appeared to have developed these comorbidities prior to AA diagnosis, suggesting that a thorough medical history screening by dermatologists at the initial visit may be appropriate.